2018
DOI: 10.1111/ene.13619
|View full text |Cite|
|
Sign up to set email alerts
|

Re‐emergent tremor in Parkinson's disease: the effect of dopaminergic treatment

Abstract: Dopaminergic treatment modified RET occurrence, severity and body distribution. Dopaminergic depletion plays a role in the pathophysiology of RET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…4 While based on appendicular rather than oculomotor data, a similar neural mechanism may account for the sequence effect in voluntary self-paced saccades in PD, although other mechanisms involving omnipause neurons or direct effects on the superior colliculus are possible. 5 In summary, our data suggest that saccadic bradykinesia can be elicited at the bedside (here also documented formally using VNG) and was apparent in all consecutive patients but absent in age-matched controls. "Saccadic bradykinesia" may be a useful and early clinical sign of PD, but future studies should confirm these findings and assess its specificity as a clinical biomarker of disease progression.…”
Section: Saccadic Bradykinesia In Parkinson's Disease: Preliminary Observationssupporting
confidence: 59%
See 1 more Smart Citation
“…4 While based on appendicular rather than oculomotor data, a similar neural mechanism may account for the sequence effect in voluntary self-paced saccades in PD, although other mechanisms involving omnipause neurons or direct effects on the superior colliculus are possible. 5 In summary, our data suggest that saccadic bradykinesia can be elicited at the bedside (here also documented formally using VNG) and was apparent in all consecutive patients but absent in age-matched controls. "Saccadic bradykinesia" may be a useful and early clinical sign of PD, but future studies should confirm these findings and assess its specificity as a clinical biomarker of disease progression.…”
Section: Saccadic Bradykinesia In Parkinson's Disease: Preliminary Observationssupporting
confidence: 59%
“…Re‐emergent tremor and resting tremor have been hypothesized to be a continuum (“tremor of stability”), 2 and they share clinical features. 5 However, re‐emergent tremor has as smaller dopamine response and slightly higher frequency than rest tremor. 4 Our data suggest that these differences may be explained by the cerebellum, which comes in with voluntary movement and transiently modulates the tremor oscillator and possibly tremor frequency, while the fundamental character of the tremor remains unchanged.…”
mentioning
confidence: 99%
“…[1][2][3] Clinical observations suggest that RET may have mechanisms similar to rest tremor. 2,[4][5][6][7] Only 1 study investigated RET pathophysiology and found that a network converging on the sensorimotor cortex could participate in RET. 8 A better understanding of RET pathophysiology may open up therapeutic strategies for a type of tremor that is often more disabling than rest tremor.…”
mentioning
confidence: 99%
“…An EMG study exploring the nature of postural tremor in PD revealed two pathophysiologically distinct clusters: 81% had re-emergent tremor and 19% had a pure postural tremor ( 111 ). The exact neural correlates of re-emergent tremor remain elusive; however, there is evidence to suggest that it overlaps with parkinsonian rest tremor in terms of frequency (both are of 3–5 Hz), the direction of movement (occasional supination-pronation), and response to dopaminergic medications ( 106 , 111 , 112 ). A recent study based on transcranial magnetic stimulation demonstrated that re-emergent tremor and rest tremor have common pathophysiological mechanisms in which the motor cortex plays an important role ( 113 ).…”
Section: Tremor In the Setting Additional Neurological Featuresmentioning
confidence: 99%